Null Hypothesis Significance Testing and p Values. Issue 4 (11th September 2017) - Travers, Jason C.; Cook, Bryan G.; Cook, Lysandra
Abstract: p values are commonly reported in quantitative research, but are often misunderstood and misinterpreted by research consumers. Our aim in this article is to provide special educators with guidance for appropriately interpreting p values, with the broader goal of improving research consumers' understanding and interpretation of research findings. Specifically, we discuss null hypothesis significance testing, describe what p values mean and how they are reported, describe some common misconceptions of p values, and provide two examples from the research literature to illustrate how p values are used in the field. Our take‐home message is that p values indicate how likely study results are to occur if the null hypothesis is true, and that p values should be cautiously interpreted.